The endemic medicinal plants of Northern Balochistan, Pakistan and their uses in traditional medicine. (15th September 2015) - Bibi, Tahira; Ahmad, Mushtaq; Mohammad Tareen, Niaz; Jabeen, Rukhsana; Sultana, Shazia; Zafar, Muhammad; Zain-ul-Abidin, Sheikh
Abstract: Ethnopharmacological relevance: The highlands of Northern Balochistan are the hot spots of medicinal and endemic plant in Pakistan. These plants are still commonly used for medicinal purposes by local people in their daily lives. This study first documented the information about the medicinal uses of endemic species of Balochistan-province Pakistan. Materials and methods: A survey was performed using open ended questionnaires, free listening and personal observations with 152 informants (54% female, 46% male). In addition, the use value (MUV), use report (UR), fidelity level (FL), frequency citation (FC), relative frequency citation (RFC), family importance value (FIV) of species were determined and the informant consensus factor (ICF) was calculated for the medicinal plants included in the study. Results: A total of 24 endemic plants belonging to 19 genera and 14 families were used by the local inhabitants to treat 12 categories of various diseases. The most common families of endemic plant species as depicted by its number of species (6 species) and FIV (9.9) was Fabaceae as the dominant family. The endemic plant species comprised perennial herbs (30%), annual herbs (25%), shrubs (29%) and under shrubs (16% each), no endemic tree species was reported in the study area. The highest number of species were used in the treatment of gastrointestinal diseases (12 species). The main route of administration is oral injection (62%) while the most frequently used form of external administration of herbal medicine was paste (5.4%) and the most commonly applied methods of preparation are powder (48.2%). Highest use report were calculated for Allium baluchistanicum and Viola makranica, (8 UR each), and least use report were calculated for two species Heliotropium remotiflorum and Tetracme stocksii (1 UR for each). Use values of the recorded plant species have been calculated which showed a highest use value of (0.73) for A. baluchistanicum and (0.56) for Berberis baluchistanica while the lowest UVs were attained for T. stocksii (0.13). Highest RFC value were calculated for Achillea millefolium (0.19) and least RFC were calculated for Blepharis sindica (0.02). The endemic species with 100% fidelity level was calculated for two plant species i.e. Seriphidium quettense and B. baluchistanica. Conclusions: The Balochistan is rich in endemic and other medicinal plants, still needs more exploration and study. Thus, it is important to document and reconstitute the remainders of the ancient medical practices which exist in Balochistan and other areas of the world, and preserve this knowledge for future generations. The endemic species which are used in traditional medicine in the region lacks phototherapeutic evidence. It is necessary to perform phytochemical or pharmacological studies to explore the potential of plants used for medicinal purposes. Overgrazing, urbanization and unsustainable harvesting of such rare and endemic medicinal plants in this region is facing severe threats of extinction. It is thus recommended that cultivation techniques be formulated, especially for the most important endemic plant medicinal species of the region. Graphical abstract: The endemic medicinal plants of Northern Balochistan, Pakistan and their uses in traditional medicine.